2009
DOI: 10.1159/000241899
|View full text |Cite
|
Sign up to set email alerts
|

Blocking the Glucocorticoid Receptor with RU-486 Does Not Prevent Glucocorticoid Control of Autoimmune Mouse Hearing Loss

Abstract: Background/Aims: Glucocorticoids effectively manage autoimmune hearing loss, although the cochlear mechanisms involved are unknown. Previous studies of steroid-responsive hearing loss in autoimmune (lupus) mice showed glucocorticoids and mineralocorticoids were equally effective, suggesting the ion homeostasis functions of glucocorticoids may be as relevant as immunosuppression for control of autoimmune-induced inner ear disease. Therefore, to better characterize the role of the glucocorticoid receptor in auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 115 publications
0
11
0
Order By: Relevance
“…Although the basis for this is undetermined, it is presumably the additive effects of the mineralocorticoid aldosterone to the mineralocorticoid impact of prednisolone. Previous studies have shown aldosterone alone will protect hearing in these mice and the glucocorticoids are effective because of their binding to the mineralocorticoid receptor (Trune and Kempton, 2009). Thus, the additional aldosterone, combined with a level of prednisolone that by itself was not enough (1.0 mg), may have sufficiently increased mineralocorticoid receptor functions sufficiently to preserve normal cochlear ion transport functions.…”
Section: Discussionmentioning
confidence: 99%
“…Although the basis for this is undetermined, it is presumably the additive effects of the mineralocorticoid aldosterone to the mineralocorticoid impact of prednisolone. Previous studies have shown aldosterone alone will protect hearing in these mice and the glucocorticoids are effective because of their binding to the mineralocorticoid receptor (Trune and Kempton, 2009). Thus, the additional aldosterone, combined with a level of prednisolone that by itself was not enough (1.0 mg), may have sufficiently increased mineralocorticoid receptor functions sufficiently to preserve normal cochlear ion transport functions.…”
Section: Discussionmentioning
confidence: 99%
“…It also has been reported that loss of aldosterone with aging may lead to presbycusis, possibly by interfering with this process26. The impact of glucocorticoids on this mineralocorticoid function also has been shown experimentally2729 suggesting the K + transport system may respond to therapeutic anti-inflammatory steroids, such as prednisone and dexamethasone.…”
Section: Ion Homeostasis In the Earmentioning
confidence: 99%
“…If inflammation disrupts stria vascularis ion homeostatic mechanisms, then therapies may treat the inflammation, the ion transport problem, or both. For example, autoimmune disease mice have significant hearing loss that develops due to elevated serum immune complexes that compromise stria vascularis ion transport [25]. The mineralocorticoid aldosterone upregulates the epithelial sodium channel (ENaC) and Na + ,K + -ATPase, and is as effective as glucocorticoids in managing or preventing this hearing loss in mice.…”
Section: Disorders Of Homeostasismentioning
confidence: 99%
“…These include the K + channels (KCNJ10, KCNE1, KCNQ1), ENaC, Na + ,K + -ATPase, NKCC, gap junctions, aquaporins, TRPV4, purinergic receptors, and tight junction claudins. Mineralocorticoids and glucocorticoids are the hormone drivers for some of these [45, 25, 3435, 56], as well as arginine vasopressin, atrial natriuretic peptide, insulin, and endothelin [57]. However, the drivers of many of these channels are thus far undetermined.…”
Section: Disorders Of Homeostasismentioning
confidence: 99%